Literature Review: The Role of School Principals’ Managerial Competence in Enhancing Teacher Work Discipline - Umi Nur Laela; Subandi; Oki Dermawan Dermawan (Journal of Educational Management Research, 2026)
This study aims to examine the role of school principals’ managerial competence in enhancing teacher work discipline and its contribution to improving teacher performance and overall school effectiveness. Using a literature review method, the study synthesizes findings from peer-reviewed journal articles published between 2021 and 2026, with a focus on leadership strategies, influencing factors, and outcomes related to teacher discipline. The findings reveal that effective principals improve teacher discipline through active supervision, motivation and reward systems, role modeling, and continuous professional development, which contribute to better punctuality, compliance with regulations, and task completion. The effectiveness of these strategies is influenced by principals’ conceptual, interpersonal, and technical competencies, supportive organizational cultures, and ongoing mentoring programs. Nevertheless, challenges such as teacher health conditions, workload pressures, resource limitations, and contextual constraints may hinder successful implementation. The study implies that strengthening principals’ managerial competence through leadership development programs, systematic supervision, and continuous professional support is crucial for improving teacher discipline, enhancing teacher performance, and promoting overall school quality.